A realworld pharmacovigilance study of trazodone based on the FDA adverse event reporting system - Yong Yu; Xin Sun; Liqun Hao; Xiaoyan Zhang; Yankui Guo (Scientific Reports)
Abstract To explore and analyze the potential adverse event (AE) signals of trazodone, with reference to the safe clinical use of drugs. Based on the FDA Adverse Event Reporting System (FAERS), the AE data of trazodone were extracted from the first quarter of 2004 to the second quarter of 2024, and the extracted data were statistically analyzed using the method, to identify valid AE signals that met our judgment, compare them with those recorded in the authorized information for trazodone thereby identifying unexpected potential adverse reactions. A total of 5199 AE reports with trazodone as the main suspect were extracted, with a higher reported proportion of females (52.68%) than males (38.83%). Many reports (31.47%) did not provide age information, although for those reports with identifiable age data, the 50–60 years age group was the most common (14.20%), and the country of reporting was predominantly the United States (82.58%). A total of 179 significant AE signals were unearthed, with suicide, formulation toxicity, abnormal penile erection, insomnia, and cardiac and respiratory arrest reported with high frequency, which was not entirely consistent with the specification record. The study unearthed 156 new potential AEs on the basis of trazodone drug inserts and suggested precautions for overdosing and dose adjustment, which is conducive to safeguarding the safety of patients’ medication.